Original paperUVB sensitivity in chronic viral hepatitis – pilot study - Wojas-Pelc, Anna; Węgrzyn, Edyta; Kulig, Piotr; Mach, Tomasz; Głowacki, Mikołaj; Surówka, Grzegorz (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
Introduction: About 3% of the Polish population suffer from chronic viral hepatitis (CVH). CVH can be present without any symptoms. Some patients manifest only extrahepatic involvement during the course of hepatitis. CVH can present with symptoms of photosensitive diseases such as LE, DM, and PCT. Aim: The aim of the study was to assess UVB sensitivity in CVH patients in comparison with lupus erythematosus (LE) patients and healthy volunteers (HV). Material and methods: The study group consisted of 90 patients: 30 with CVH, 30 with LE and 30 HV. We performed phototesting in NB and BB UVB radiation and determined MED and the >1 MED erythema duration. Results: A significant difference (p=0.01) was found between mean MED BB and NB UVB in subjects with LE and HV. Mean persistence time of >1 MED erythema was significantly different between LE patients and HV (p<10–6) and between CVH and HV (p<10–6). There were no significant differences in phototesting values between patients with CVH type B and CVH type C, between patients with normal or higher aminotransferase activity and between patients treated or untreated. Conclusions: Our study revealed increased photosensitivity in CVH patients, especially in persistence of >1 MED erythema. This value was similar as in LE patients. There were no correlations between virus type, liver enzymes activity, treatment and phototesting results. Photosensitivity could be one of the extrahepatic manifestations of CVH.